Oscillatory boundary layer over fixed rough beds - Borghei, S.M. (1982)
The accurate study of characteristics of the flow under gravity waves has become of prime importance due to the growing demand for structural engineering designs in the coastal environment. Although many investigations have been carried out, the progress of fundamental research was slow due to the lack of an adequate velocity measuring instrument. However in recent years, the development of the Laser Doppler Velocimeter has made it possible to observe the orbital velocity very close to a bed without disturbing the flow. This technique was used in this investigation, in which observations of the oscillatory flow under gravity waves were carried out above smooth, two-dimensional and three-dimensional rough beds.